Odpowiedzi

2009-11-19T22:46:09+01:00
8⁻³×(8⁻³)²= 8⁻³×8 do minus 6 potegi =8 do minus 9 potegi


(9³×9²)⁻³÷(9⁴×6⁻²)⁻³=(9 do minus 9 potegi x 9do minus 6 potegi) : (9do minus 12 potegi x 6do plus 6 potegi)


9⁻³×9³= 9do minus 9 potegi

[68-(10-4)×8]×(-2)=[68-(6)x8]x(-2)= [68 +48]x(-2)= 116x2= 232
2009-11-20T01:24:48+01:00
8⁻³×(8⁻³)²= 8⁻³ *8⁻⁶ = 8⁻⁺

(9³×9²)⁻³÷(9⁴×6⁻²)⁻³ = (9⁵ )⁻³: (9⁻¹²*6⁶) = 9⁻¹⁵ :9⁻¹²:6⁶ = 9⁻³:6⁶

9⁻³×9³ = 9° =1

[68-(10-4)×8]×(-2)= [68-(6) *8]*(-2) = [68 -48] *(-2) = 20*(-2) = -40